2019
DOI: 10.3390/toxins12010023
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Ochratoxin A-Induced Apoptosis in Differentiated Caco-2 Cells

Abstract: Ochratoxin A (OTA), an important mycotoxin that occurs in food and animal feed, has aroused widespread concern in recent years. Previous studies have indicated that OTA causes nephrotoxicity, hepatotoxicity, genotoxicity, immunotoxicity, cytotoxicity, and neurotoxicity. The intestinal toxicity of OTA has gradually become a focus of research, but the mechanisms underlying this toxicity have not been described. Here, differentiated Caco-2 cells were incubated for 48 h with different concentrations of OTA and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…The intestinal epithelium is the first site of exposure following mycotoxin ingestion and may be exposed to higher concentrations than other tissues [ 17 ]. Changes in villus height reflect the balance between intestinal epithelial cells (IEC) proliferation and apoptosis [ 89 , 107 ], which is in line with findings that several mycotoxins can cause oxidative stress induced IEC apoptosis and cell cycle arrest both in vivo and in vitro [ 108 110 ]. Previous studies suggested effects of mycotoxins on the intestinal morphology may appear to be section-specific, with effects on duodenum and jejunum being more pronounced than ileum [ 49 , 57 , 89 , 111 ].…”
Section: Nutritional Impact Of Major Mycotoxinssupporting
confidence: 56%
“…The intestinal epithelium is the first site of exposure following mycotoxin ingestion and may be exposed to higher concentrations than other tissues [ 17 ]. Changes in villus height reflect the balance between intestinal epithelial cells (IEC) proliferation and apoptosis [ 89 , 107 ], which is in line with findings that several mycotoxins can cause oxidative stress induced IEC apoptosis and cell cycle arrest both in vivo and in vitro [ 108 110 ]. Previous studies suggested effects of mycotoxins on the intestinal morphology may appear to be section-specific, with effects on duodenum and jejunum being more pronounced than ileum [ 49 , 57 , 89 , 111 ].…”
Section: Nutritional Impact Of Major Mycotoxinssupporting
confidence: 56%
“…Differentially expressed pathways were verified by Western blot. Protein extraction and Western blot were performed as previously mentioned (Yang et al., 2019). Antibodies were used according to the manufacturer's instruction: NF‐κB p65, pNF‐κB p65, ERK, pERK1/2, JNK (Cell Signaling Technology), pJNK1/2 (Invitrogen), and goat anti‐rabbit IgG/HRP (Bioss).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, AFM1 and OTA inhibited the cell viability of the co-culture of Caco-2/HT29-MTX [ 43 ]. Equally, OTA promoted apoptosis in IPEC-J2 and Caco-2 cells by inducing mitochondrial reactive oxygen species (ROS) and arresting the cell cycle [ 81 , 82 , 83 ]. Apart from mycotoxin effects in human intestinal cells, DON inhibited intestinal epithelial cell viability and induced apoptosis in rat and pig cell models [ 84 , 85 , 86 , 87 , 88 ].…”
Section: Intestinal Dysfunction Induced By Mycotoxinsmentioning
confidence: 99%